Sulfur Cycling in an Iron Oxide-Dominated, Dynamic Marine Depositional System: The Argentine Continental Margin - Riedinger, Natascha; Brunner, Benjamin; Krastel, Sebastian; Arnold, Gail L.; Wehrmann, Laura M.; Formolo, Michael J.; Beck, Antje; Bates, Steven M.; Henkel, Susann; Kasten, Sabine; Lyons, Timothy W. (Frontiers in Earth Science, 2017)
The interplay between sediment deposition patterns, organic matter type and the quantity and quality of reactive mineral phases determines the accumulation, speciation, and isotope composition of pore water and solid phase sulfur constituents in marine sediments. Here, we present the sulfur geochemistry of siliciclastic sediments from two sites along the Argentine continental slope—a system characterized by dynamic deposition and reworking, which result in non-steady state conditions. The two investigated sites have different depositional histories but have in common that reactive iron phases are abundant and that organic matter is refractory—conditions that result in low organoclastic sulfate reduction rates (SRR). Deposition of reworked, isotopically light pyrite and sulfurized organic matter appear to be important contributors to the sulfur inventory, with only minor addition of pyrite from organoclastic sulfate reduction above the sulfate-methane transition (SMT). Pore-water sulfide is limited to a narrow zone at the SMT. The core of that zone is dominated by pyrite accumulation. Iron monosulfide and elemental sulfur accumulate above and below this zone. Iron monosulfide precipitation is driven by the reaction of low amounts of hydrogen sulfide with ferrous iron and is in competition with the oxidation of sulfide by iron (oxyhydr)oxides to form elemental sulfur. The intervals marked by precipitation of intermediate sulfur phases at the margin of the zone with free sulfide are bordered by two distinct peaks in total organic sulfur (TOS). Organic matter sulfurization appears to precede pyrite formation in the iron-dominated margins of the sulfide zone, potentially linked to the presence of polysulfides formed by reaction between dissolved sulfide and elemental sulfur. Thus, SMTs can be hotspots for organic matter sulfurization in sulfide-limited, reactive iron-rich marine sedimentary systems. Furthermore, existence of elemental sulfur and iron monosulfide phases meters below the SMT demonstrates that in sulfide-limited systems metastable sulfur constituents are not readily converted to pyrite but can be buried to deeper sediment depths. Our data show that in non-steady state systems, redox zones do not occur in sequence but can reappear or proceed in inverse sequence throughout the sediment column, causing similar mineral alteration processes to occur at the same time at different sediment depths.